Assisting Salted Fish Entrepreneurs in Managing Raw Material Costs, Inventory, and Competitive Strategy to Increase Income in Bagan Arya Village - Saputri, Aulia Habibi; Imsar, Imsar; Daulay, Aqwa Naser (LP2M INSURI Ponorogo, 2025)
In Indonesia, the growth of Small and Medium Enterprises (SMEs) is driven by high revenues. The background of this study is based on the declining revenue among salted fish entrepreneurs due to fluctuations in raw material costs, unstable raw material availability, and intense competition in the local market. This study aims to analyze the effect of raw material costs, raw material inventory, and the level of competition on the income of salted fish entrepreneurs in Bagan Arya Village. This study uses a quantitative approach with a survey method through interviews involving 30 salted fish entrepreneurs as a sample. Panel data is used because it is able to capture changes and relationships between variables more accurately over a five-year observation period. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with the SmartPLS 4.0 application. The research findings revealed that raw material costs and raw material inventory have a positive and significant effect, while competition has a negative and significant effect on revenue. The R-squared value of 0.745 indicates that raw material costs, raw material inventory, and competition simultaneously explain 74.5% of revenue. These results highlight the importance of cost and inventory management strategies, as well as innovation in the face of competition, to increase the income of local entrepreneurs in the salted fish processing sector.